Influência da adição de BaTiO3 nas propriedades estruturais, elétricas e anelásticas de cerâmicas piezoelétricas de Bi0,5Na0,5TiO3-BaTiO3 - Diaz, Julio Cesar Camilo Albornoz (2014)
Motivated by the great growth presented in the last decade in research on lead-free piezoelectric ceramics and the fact that some ceramic systems, as those based on bismuth, have been identified as promising candidates to substitute the lead zirconate titanate (PZT) in their present technological applications, was proposed as the objective of this work, study the effect of adding 𝐵𝑎𝑇 𝑖𝑂3 (BT) on the structural, electrical and anelastic properties exhibit by the system (1−𝑥)𝐵𝑖0.5𝑁𝑎0.5𝑇𝑖𝑂3−𝑥𝐵𝑎𝑇 𝑖𝑂3 (BNT-BT). The structural characterization was performed by the techniques of X-ray diffraction (XRD) and Raman spectroscopy. The morphological and compositional aspects (qualitative), in the calcined powders, and the sintered samples were studied by scanning electron microscopy (SEM). The ferroelectric and dielectric character of the compositions were obtained through characterization of ferroelectric hysteresis exhibit and using the technique of electrical impedance spectroscopy, respectively. Phase transitions and the possible mechanisms of anelastic relaxation were studied by the technique of mechanical spectroscopy. Samples were obtained by the method of solid state reaction, where it was possible to obtain compositions with 0.00 ≤ 𝑥 ≤ 0.08 with relative density greater than 95% and without the presence of spurious or secondary phases. On profiles of X-ray diffraction for the different studied sintered compositions was applied the method of Rietvelt refinement which allow the determination and confirmation of the crystal structures in the samples under study, and the presence of a morphotropic phase boundary (MPB) for the BNT-BT. The XRD results were corroborated by the results of Raman spectroscopy. The ferroelectric nature of the different compositions of BNT-BT system studied was confirmed. Electrical phase transitions (F-Af and Af-P) and structural transitions (R-T and T-C) exhibited by the BNT-BT were characterized by mechanical spectroscopy (using a dynamical mechanical analyzer (DMA)), and by electrical impedance spectroscopy, employing the results in complementing the electrical and structural phase diagram of this system. In addition to the phase transitions obtained, the technique of mechanical spectroscopy for compositions between 0.00 ≤ 𝑥 ≤ 0.03, allowed the observation of a complex process of anelastic relaxation that was associated with interactions and mobility of different defects present, which possibly contribute significantly to an increase of conductivity in these materials, which had not been previously reported in the literature.